(untitled) (Actualizaciones en Sida e Infectología, 2023)
Nearly a century after the discovery and subsequent development of antimicrobials, the dramatic problem of antimicrobial resistance (AMR) is a challenge that affects and expands across a broad ecosystem (human, animal and environmental health). Considering also that the discovery of new drugs has slowed down in the last 20 years, there is a growing interest in alternative approaches to mitigate the effects of AMR (1-4). Known for more than 100 years, the development of phages has been overshadowed by the use of antibiotics. They are considered the most abundant biological entities on the planet, and are used in the food industry for the elimination of the main enteropathogenic bacteria (2, 4-6). In this issue of ASEI, Dr. Guzzi provides a detailed update (expected and necessary) on the characteristics of phages, in order to think about their role in the current context of AMR in Argentina and the region. Phages have a bactericidal effect, with low influence on the intestinal microbiota, no cross-resistance to antibiotics and no tropism towards mammalian cells. Furthermore, their effects could extend to other microorganisms, such as adenoviruses and Aspergillus spp (6, 7). Its activity on the biofilm allows us to consider its use in infections that are difficult to resolve (cystic fibrosis, urinary tract infections associated with lithiasis or urinary devices, diabetic foot, among others). Oral administration would allow its use for gastrointestinal decolonization of resistant germs or selective decolonization in critically ill patients, and for the treatment of C. difficile infection. Other possible uses are the cleaning of surfaces in the hospital environment and the sanitation of contaminated effluents. Considering the low environmental impact of phages, their use in animal health opens up prospects of interest. In short, their applications could be broad and widespread, appealing to resourcefulness and creativity. However, certain questions still remain. If they are ubiquitous, do they act on the multidrug-resistant bacteria that contaminate effluents? Are there phages in the water and food we consume? What effect do they have on us, if any? Among the technical aspects, the administration of suspensions obtained only by filtration (which do not remove all bacterial components) is a safety issue that could be circumvented with more precise manufacturing methods, as is the innate ability to transfer DNA from one bacterium to another, thus contributing to virulence and resistance factors. In relation to the determination of the so-called “phagogram,” some experts propose the creation of reference centers in each region, as well as phage libraries in each hospital in order to perform sensitivity tests, as it is the case today with antibiotics (4, 8). The probable superiority of phage combination over monotherapy, as well as anti-inflammatory versus pro-inflammatory effects (which could intervene in the inflammatory cascade of sepsis), are a matter of discussion. If administered systemically, are they safe for patients with different types of immune disorders? (6, 7) As for their PK/PD characteristics, one may wonder how to maintain a sufficient amount of phages in the blood for long enough to treat bacteremia infections, or how many phages are needed to treat high-inoculum infections. Its interaction with the immune system is also linked to the development of neutralizing antibodies. Could the presence of the latter decrease the ultimate efficacy of phages? On the other hand, the active dose of orally administered phages may be reduced by gastric acidity and proteolytic activity. “new-old” paradigm of phages; the accessibility of this therapy as a key point (although in Argentina there are several groups working on the subject for decades, especially in the food industry, who are willing to share their experience to apply in human health, in line with the translational approach in medical sciences); and the choice of this therapy as an “alternative” or complement to antibiotics will be evaluated according to the clinical situation. In this sense, it offers an interesting possibility in terms of “personalized medicine,” in which phage therapy could be a good example of this trend. We join the reflection of certain authors who ask whether, in the current situation of AMR (we could also add: in impoverished countries with limited or heterogeneous access to new drugs, which are always expensive), it is still ethically acceptable not to use this tool in adequately evaluated scenarios. With less evidence than that which has existed on phages for more than 100 years, older drugs (e.g. colistin), which we learned about through their application, have been brought back into use. How much longer is it prudent to wait before getting down to phage therapy? In this regard, and in relation to regulatory aspects, multiple factors must be considered, but it would be desirable to facilitate compassionate use, for example, where the treatments administered have failed. Since they are biological entities, a regulation similar to those applied to live-attenuated viral vaccines could also be considered. From now on, an adequate record of its use is required as a contribution to the understanding of the functioning of this therapeutic tool and its products (endolysins). Lastly, will AI be able to help in the decision-making process? The pressing problem of AMR calls for the rapid implementation of different strategies. Guzzi’s review has succeeded in making us become familiar with such tools and will spark the readers’ interest. Available data on compassionate use in humans support the initial screening of the combination of phage and antibiotics. Recent advances in phage purification and formulation will contribute to improve the efficacy and safety of this therapy. It will probably not be the definitive solution, but it is an approach of great interest to be applied in the short and medium term in our country through collaborative initiatives with different actors (both local and from other countries): health authorities, scientific societies, universities, pharmaceutical companies and working groups such as INVERA, in the unequal race against RAM. The author announces phage therapy as an “alternative” to antibiotics. Further on, she firmly states her opinion that “bacteriophages stand as the best solution” to combat AMR. In this regard, some reflections are in order. It will be necessary to overcome several barriers: the acceptance among the medical community of the